CIPP Model-Based Evaluation of the Education System to Improve Learning Quality at Muhammadiyah Islamic Elementary School Sidokerto, Plupuh - Isnaini; Siti Halimah; Budi Murtiyasa; Sumardi (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
This study evaluates the education system in improving learning quality at Muhammadiyah Islamic Elementary School Sidokerto, Plupuh, using the Context, Input, Process, and Product model. It employed a qualitative approach with an evaluative case study design. Data were collected through semi-structured interviews, non-participant observations, and document analysis. Participants were selected purposively and included the principal, curriculum coordinator, teachers, administrative personnel, school committee representatives, parents, and students. Data were analyzed through data condensation, data display, and conclusion drawing and verification. The findings show that the context component was aligned with students’ academic needs, Islamic character development, and Muhammadiyah institutional values. The input component was generally adequate, although digital facilities, teacher professional development, and resource allocation required improvement. The process component indicated that learning, assessment, academic supervision, and parental communication had been implemented, but differentiated instruction and supervision follow-up remained inconsistent. The product component revealed positive development in student participation, discipline, religious habituation, and teacher collaboration. However, the school had not fully integrated academic, behavioural, professional, and stakeholder satisfaction data into a longitudinal evaluation system. The study concludes that learning quality improvement requires a continuous, participatory, measurable, and evidence-based CIPP evaluation cycle.